2020
DOI: 10.7554/elife.56434
|View full text |Cite
|
Sign up to set email alerts
|

A novel function of R-spondin1 in regulating estrogen receptor expression independent of Wnt/β-catenin signaling

Abstract: R-spondin1 (Rspo1) has been featured as a Wnt agonist, serving as a potent niche factor for stem cells in many tissues. Here we unveil a novel role of Rspo1 in promoting estrogen receptor alpha (Esr1) expression, hence regulating the output of steroid hormone signaling in the mouse mammary gland. This action of Rspo1 relies on the receptor Lgr4 and intracellular cAMP-PKA signaling, yet is independent of Wnt/β-catenin signaling. These mechanisms were reinforced by genetic evidence. Luminal cells-specific knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Notably, in the control group ESR1 was mainly located in the nucleus, while in the baicalin-treated group ESR1 localized to the cytoplasm ( Figure 4G ). To investigate whether baicalin regulates the transcription of Esr 1, we utilized a luciferase reporter driven by the proximal promoter of mouse Esr1 ( Geng et al, 2020 ). We found that luciferase activity was down-regulated by baicalin in a dose-dependent manner ( Figure 4H ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in the control group ESR1 was mainly located in the nucleus, while in the baicalin-treated group ESR1 localized to the cytoplasm ( Figure 4G ). To investigate whether baicalin regulates the transcription of Esr 1, we utilized a luciferase reporter driven by the proximal promoter of mouse Esr1 ( Geng et al, 2020 ). We found that luciferase activity was down-regulated by baicalin in a dose-dependent manner ( Figure 4H ).…”
Section: Resultsmentioning
confidence: 99%
“…The Procr and Esr1 promoters were separately cloned into the pGL4.17 vector to generate the luciferase reporters ( Geng et al, 2020 ). 293T cells were plated into 24-well tissue culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…6 The activation of β-catenin is accompanied by the loss of mito- could be activated by Wnt-triggered inhibition on its degradation 35 and also could be stimulated by GPCR-induced signal wave. 15,36,37 Interestingly, we have found several GPCRs such CXCR4 and CB2 induce the kidney injury depending on β-catenin activation. 15,36 CB2 was recently found to be primarily upregulated in the proximal and distal tubules in renal fibrosis model and promoted kidney fibrosis by orchestrating β-catenin signalling, as reported by our recent work.…”
Section: Discussionmentioning
confidence: 96%
“…The activation of β‐catenin is accompanied by the loss of mitochondria mass and overproduced ROS, suggesting the highly intimate correlation of β‐catenin with mitochondrial dysfunction. β‐catenin could be activated by Wnt‐triggered inhibition on its degradation 35 and also could be stimulated by GPCR‐induced signal wave 15,36,37 …”
Section: Discussionmentioning
confidence: 99%
“…A recent work reports that R-spondin 1 (RSPO1), a niche factor secreted by the ERα-negative luminal cells, regulates ERα expression through paracrine mechanisms [197]. RSPO1 is known to bind LGR receptors and synergize with WNT4 to enhance Wnt/βcat signaling in mammary basal cells.…”
Section: Erα + Unipotent Stem Cellsmentioning
confidence: 99%